COMPARISON OF OUTCOME OF INTRAPERITONEAL INSTILLATION OF ROPIVACAINE VERSUS NORMAL SALINE FOLLOWING LAPAROSCOPIC CHOLECYSTECTOMY IN TERMS OF POSTOPERATIVE PAIN ANALGESIA REQUIREMENT (The Research of Medical Science Review, 2025)
Gallbladder diseases, managed surgically for over 2000 years, have seen laparoscopic cholecystectomy emerge as the gold standard due to reduced pain and faster recovery. However, effective postoperative pain control remains a challenge, necessitating optimized interventions like intraperitoneal ropivacaine. Given the limited local data, our study aimed to evaluate and establish the efficacy of ropivacaine in reducing postoperative pain and analgesic requirements. OBJECTIVE: To compare the outcome of intraperitoneal instillation of ropivacaine versus normal saline for reduction of postoperative pain after laparoscopic cholecystectomy SETTING: North Surgical ward, Mayo hospital Lahore DURATION: Six months after the approval of synopsis from: May 2, 2024 to November 2, 2024 STUDY DESIGN: Randomized control trial METHODOLOGY: In this trial we included patients with symptomatic gallstones undergoing laparoscopic cholecystectomy, randomly assigned to receive 30 mL of either 0.5% ropivacaine (Group R) or saline (Group NS) in the gallbladder bed. Pain was assessed at 6 hours using the Visual Analogue Scale (VAS) by independent, blinded assessors. Additional analgesia was administered for VAS scores >6, with data on demographics, pain, and analgesic requirements meticulously recorded for analysis. RESULTS: The ropivacaine group showed significantly lower mean VAS scores (1.98 ± 0.84) compared to the saline group (5.60 ± 1.21; p < 0.000). Rescue analgesia was required by 30% in the ropivacaine group versus 60% in the saline group (p = 0.003), demonstrating ropivacaine’s superior efficacy in reducing postoperative pain and analgesic needs. CONCLUSION: Outcome of intraperitoneal instillation of ropivacaine is significantly favorable when compared to those with normal saline for reduction of postoperative pain after laparoscopic cholecystectomy.